Dendrite injury triggers neuroprotection in Drosophila models of neurodegenerative disease. - Prange, S.E.; Bhakta, I.N.; Sysoeva, D.; Jean, G.E.; Madisetti, A.; Le, H.H.N.; Duong, L.U.; Hwu, P.T.; Melton, J.G.; Thompson-Peer, K.L. (Scientific reports, 2024)
Dendrite defects and loss are early cellular alterations observed across neurodegenerative diseases that play a role in early disease pathogenesis. Dendrite degeneration can be modeled by expressing pathogenic polyglutamine disease transgenes in Drosophila neurons in vivo. Here, we show that we can protect against dendrite loss in neurons modeling neurodegenerative polyglutamine diseases through injury to a single primary dendrite branch. We find that this neuroprotection is specific to injury-induced activation of dendrite regeneration: neither injury to the axon nor injury just to surrounding tissues induces this response. We show that the mechanism of this regenerative response is stabilization of the actin (but not microtubule) cytoskeleton. We also demonstrate that this regenerative response may extend to other neurodegenerative diseases. Together, we provide evidence that activating dendrite regeneration pathways has the potential to slow-or even reverse-dendrite loss in neurodegenerative disease.